Synthesis and characterization of 3-methyl-1-butene homo- and copolymers - Joubert, D. J.(Dawid Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.